Antihypertensive Effect of Polyphenol-Rich Fraction of Azadirachta indica on Nω-Nitro-L-Arginine Methyl Ester-Induced Hypertension and Cardiorenal Dysfunction - Omóbòwálé, Temidayo Olutayo; Oyagbemi, Ademola Adetokunbo; Ogunpolu, Blessing Seun; Ola-Davies, Olufunke Eunice; Olukunle, Johnny Olufemi; Asenuga, Ebunoluwa Racheal; Ajibade, Temitayo Olabisi; Adejumobi, Olumuyiwa Abiola; Afolabi, Jeremiah Moyinoluwa; Falayi, Olufunke Olubunmi; Ashafa, Anofi; Adedapo, Adeolu Alex; Yakubu, Momoh Audu (Drug Research, 2019)
Azadirachta indica (AI) is a medicinal plant with reported antioxidant and cardio-protective properties. The use of plant-based polyphenols has become greatly increased in the last one decade. The present study investigated the protective effect of the polyphenol-rich fraction (PRF) of the methanol-extract of Azadirachta indica against Nω-Nitro-L-Arginine Methyl Ester (L-NAME) induced hypertension and cardiorenal dysfunction in rats. Fifty (50) Wistar albino rats were grouped into five groups. Group A, the control, was administered potable water. Groups B-E received orally, 40 mg/kg of L-NAME only, 40 mg/kg of L-NAME and 100 mg/kg of AI extract, 40 mg/kg of L-NAME and 200 mg/kg of AI extract, and 40 mg/kg of L-NAME and 25 mg/kg of captopril, respectively for 21 days. The results of the present study revealed that L-NAME administration led to a significant increase in systolic blood pressure, diastolic blood pressure, and mean arterial blood pressure. Markers of oxidative stress (malondialdehyde,protein carbonyl) increased significantly while there was reduction in reduced glutathione level, activities of superoxide dismutase, glutathione peroxidase and glutathione-S-transferase as well nitric oxide bioavailability. Immunohistochemistry revealed higher expressions of nuclear factor kappa beta (NF-kB) and kidney injury molecule 1(Kim-1) and lower expressions of nuclear factor erythroid 2–related factor 2 (Nrf2) in hypertensive rats. Our results indicated that with PRF of AI restored high blood pressure, reduced markers of oxidative stress, normalized serum NO bioavailability and increased the expressions of Nrf2. Hence, PRF of Azadirachta indica could be used for the treatment of hypertension.
Keywords: Azadirachta indica; hypertension; oxidative stress; renal damage; cell signaling